The politics of new social movements Services, Land & Human Rights: Anti-Capitalist Struggles in Pre and Post-Apartheid South Africa - Barrett, James Andrew (My University, 2006)
“The longing for a better world will need to arise at the imagined meeting place of many movements of resistance, as many as there are sites of enclosure and exclusion. The resistance will be as transnational as capital. Because enclosure takes myriad forms, so shall resistance to it.” - Iain A Boal, First World, Ha Ha Ha!, City Lights, 1995 Boal’s description captures the exuberance, hope and confidence of today’s social movements. That there is something irresistible about autonomous, grassroots and subaltern movements in their anti-systemic alternatives to capitalism has become a notion which has gained considerable currency in recent years.1 Formations of these groups (the Zapatistas being the oft cited example) are seen to mirror theories of the most utopian and radical forms of democracy. In Part 1 we seek to examine a range of critical historiography in exploring the features of what is ‘new’ in today’s social movements, using Zapatista style organization and discourse as the prototype. This definition will be moulded with the elements of critical theory which have at their core a radical transformative function of social movements. For example Castells’ work on urban movements pictures: “collective conscious action aimed at the transformation of the institutionalized urban meaning against the logic, interest and values of the dominant class.”2 We will draw from Murray’s assumption that such movements “actively contest the prevailing forms of political representation and the legitimacy of political rule.”3 New social movements (NSM) will be seen within the context of anti-normative approaches to democracy. An alternative pole of reference will emerge in contrast to what we will term low intensity, liberal, parliamentary or bourgeois forms of democracy. All this will be lodged in an understanding of old social movements. We hold these to be single issue movements that fail to forge links to other sites of oppression and exploitation, or movements which take on a narrow class composition and understanding of change. Implicit in moving on from narrow, and or,Marxist-Leninist positions over class, is the multiplicity of relations humans have within the social body. This refutes crude economism conceptions regarding the make-up of the working class.4 However, capitalism and our relations to production, still remain central in understanding the relationship of the subject to the social body. We suggest recent crisis points and weaknesses in capitalism (detected as neo-liberal trends) provide plenty of scope for weaving an historical dialectic back in. Evidence for this comes from critical theory which claims, perhaps falsely, to be founded on anti-essentialism.5 We argue that it is commodification which breeds this resistance against the totalizing effect of capitalism at every level of the structure. Thus neo-liberalism embodies for much of this critical thought the subject of a “Fourth World War” fought by the multitude. 6 The mobile nature of contemporary capital and the immaterial essence of its production to define the multitude – essentially disenfranchised and disaffected subjects – has led to an expanded definition of the old working class.7 The multitude is the reinvention of some social subject invested in an historical project. This multitude has taken on a particular guise, moving away from traditional conceptions of a revolutionary class. As Negri and Hardt note: “The closer we look at the lives and activity of the poor, the more we see how enormously creative and powerful they are”.8 The poor embody the ontological condition not only of resistance but also of productive life itself.9 However, we will also attempt to locate moments within the subject that go beyond the indeterminacies and moments of rupture within the structure. Careful attention will be paid to Zizek’s subject of lack, in assessing the carnivalesque and irrational moments of today’s movements and the role of what we will view as a renewed sense of voluntarism. We remain conscious that we are forging a vision of new social movements which forges an at times uneasy alliance across a variety of groups who challenge dominant structures at different times, spaces and ways. It is sometimes tempting to lump various “anti-globalisation” groups together, without grasping the intricacies and nuances that bind as well as divide them. Ultimately, we accept some of the essentialist critique that can be levelled at NSM theory, recognizing a trope of romanticism around struggle is deliberately and necessarily invented. This will be fully discussed in the controversial claim that some movements and elements of civil society have more validity than others. It will be considered in claiming that moments of oppression, subordination and exploitation require articulation and don’t erupt into historical trajectories of struggle. This requires the development and expression of relative rather than fixed universals (e.g. around democracy, right to water, right to land). It is commodification and neo-liberalism that provides the stimulus for such relative universals. We shall see that they revolve around issues that are real to subjects in the narratives of their struggles and lives.11 Finding some fixity of meaning and experience ensures our analysis is not post-structuralist. Post-structuralism has fostered awkward relationships with truths which have, as Mamdani has noted, not always led to a basis of a “healthy humanism”.12 It leads to a universalized aestheticization whereby truth, reduced to merely a style effect of discursive articulation, forges an endless spectrum of interpretation/re-interpretation. 13 Moreover, it can be utilized to create legitimacy for fascist, colonialist and imperialist discourses. Part 1 attempts to provide the basis for the rest of the work by developing an understanding of the historicity of new social movements and what makes them different to other forms of political and social organisation. This is critical for later discussion which will draw upon the experiences of South Africa. In Part 2 we seek to build from the radical civil society theory and tease out features and characteristics of it within anti-apartheid social movements. This will involve an exploration around township civics which were and are often bundled under the umbrella of the United Democratic Front (UDF). Many of these were built around notions of People’s Power, economic transformation and social justice. We will consider the ideology present in these movements and how it played out in realities, acknowledging the highly repressive scenario of the apartheid state. Within these movements we will flesh out radical spaces and visions which appeared to have dissipated in the ANC hegemony over the decolonisation process and subsequent “transformation” project. We will not shy away from advocating that there were features within such radical spaces, such as Charterist, and or, unity projects, which emerged at various times to create implicitly anti-democratic politics. 14 Such problems as we will see went to the core of the UDF and also into the geo-polities of South Africa which became “ungovernable” in the 1980s. Depoliticization was not just a performative effect of ANC strength or “Stalinism” as often narrated by the left, but a weakness in the structure and formation of civil society. 15 We explore whether it was not just the ANC that “demobilized” the grassroots, but that the form and functioning of civil society that contributed to the conditions in which movements’ own radical notions of People’s Power and direct democracy dissipated. Part 3 will look at this demobilization within the context of the transition to democracy during the negotiated settlement.16 We scrutinize the nature of the period from apartheid to liberal democracy, noting trajectories of struggle which mark both eras. We argue that elements and goals in the struggle that sought a very different democracy to that gained at the CODESA talks have re-emerged in the deepening disillusionment of the ANC project after ten years of governance. This has within some discourse included the ability of the nation-state generally, within neo-liberalism, to bring about social justice. Yet, the suggestion that this is the period of “economic” rather than “racial” apartheid will need to be carefully explored in the context of Fanon’s characterization of national liberation elites.17 While noting the benefit an economic approach has in distinguishing the role of dominant classes, we suggest it can overshadow explicit structures of racism that penetrate to the core of South African society. They are brought out for example by grassroots movements such as the Landless People’s Movement (LPM), in their campaign that equated landlessness with racism. Finally Part 4 examines the extent characteristics we ascribe to the new social movements of South Africa correspond with the features of anti-apartheid struggles of the 1980s. Moreover, it requires us to assess the critical theory developed in Part 1 in terms of realities in post-Apartheid South Africa. We note the apprehension in considering parallels between anti-apartheid struggles and current rights based struggles. While there have been a few attempts to make links within a continuation of struggle from apartheid to neo-liberalism18, all too often, the anti-apartheid struggles that invoked notions of People’s Power have been dismissed as undemocratic, authoritarian and reactionary.19 While an attempt to wipe the slate clean might be useful in carving out a fresh and dynamic image for contemporary social movements, it perhaps ignores that there are similar issues, rhetoric and ideologies being played out today. We will explore whether the historiography simply seeks to justify and re-create contemporary social movements to create ammunition for particular strands of political theory judged to be liberationist and correct within the current historical juncture. Are we carving out a fictional historicity within the identity of struggle that doesn’t exist? Are narratives created more for attachments to a belief in certain “historical” processes than less sharply defined realities? Is the multitude, merely Marx’s 19th century industrial working class, vested with an imaginary historical project? Noting the background of many individuals involved within the APF (trade union, SACP), we need to discuss how they have been placed on a new trajectory of thought given the features which define today’s subjects in NSM compared to orthodox Marxist-Leninist thought around the revolutionary subject. We hope a sketch of the past and an analysis of the present may contribute in the current debates within the social movements during a critical time for anti-capitalist struggles in South Africa. This work is not concerned with producing exhaustive lists of repressive acts conducted by the state, the brutality of private security firms, or broken election promises, but in uncovering the structure of the post-apartheid state and how social movements respond and re-create themselves. Despite their youth, they represent the first serious contestation of ANC hegemony in terms of an alternative discourse around democracy, social justice and transformation. This work has been made possible through regular contact with social movements in Gauteng. Informal participatory discussions with various activists and communities within these struggles have been invaluable and enlightening. Such first hand experience has provided an insight into the operative nature and democratic functioning of a variety of movements including the role of vanguards and leadership. My attendance at various forums and discussions, such as the Social Movements Indaba (SMI), has also been vital. Fundamentally, the work hinges upon a critical exploration from three areas. Firstly, in the discussion necessary to establish a historicity of new social movements which will point to their methodological and epistemic construction. Secondly, upon an understanding of the South African experience that can cover an immense ground from apartheid into liberal-democracy which is aware and responsive to a wide range of historiography. Thirdly, a series of interviews and personal reflections from discussions with various activists across South Africa. Some are well known leaders. Others form part of the collective multitudes beginning to emerge and speak through the fissures of South African society. Relationships that I have made, as well as recent political events, culminated in the choices of the Khayelitsha township of Cape Town, Alexandra in Johannesburg and Harrismith in the Free State as the sites for this part of the research.21 The methodology hinges upon an accurate reflection and assessment of contemporary social movements from the people who participate and function within them, together with an historiographical account of social movements in the South African experience. Limitations here are perhaps obvious. Interviewees may have the tendency to be modest or emphasize their own personal role in struggles. Attendance of community meetings and forums is hoped to counter-balance this together with the use of contemporary subject work. However, there can be no objective yardstick by which to judge the contributions found in this paper. Furthermore, the lack of rigour within the methodology would alarm the majority of modernist and positivist historians and commentators. Yet, it is with this aim that the work attempts to accept the criticisms of romanticism, myth, euphoria and narratives in seeking to forge the very conditions outlined by Boal in which we might find the same “imagined meeting place” and discussion of freedom.
Student Number : 0419886N - MA research report - School of Politics - Faculty of Arts
Keywords: Social Movement Politics; Democracy; Civil Society Under Apartheid; Struggles Against Apartheid; Post-Apartheid South Africa